Pengembangan Media Pembelajaran Komikita Berbasis E-Komik Materi Hak dan Kewajiban Pada Kelas V - Magfiroh, Lailatul; Asmarani, Ratih; Dwinata, Anggara (IJPSE Indonesian Journal of Primary Science Education, 2024)
Development of E-Comic based comic media for learning rights and obligations at home and at school to shape the character of fifth grade elementary school students. Because in schools there are many students who do not understand their rights and obligations. As well as developing comics to introduce technology to students because it is not yet optimal in the use of technology in learning. The type of research implemented by researchers applies the type of ADDIE model developed by Rahmadhany, which has five systematic stages, namely analysis, design, development, implementation and evaluation. The subjects in this study were class V- A students at SDN Kepanjen 2 Jombang for the 2022/2023 academic year. The instrument obtained data using field notes, media validation sheets, student response questionnaires, tests and documentation. The data collection technique for measuring the validity of the media uses a material and media validation questionnaire that is assessed by validator experts. As well as the response of teachers and students after using E-Comic learning media. As well as in measuring understanding of the material using tests. On the quality of E-comic learning media, it obtains an average value of 96.25% with very valid criteria. In terms of material validity, a score of 87.5% is obtained with very valid criteria. And there are student and teacher responses with an average of 88.78% with very valid criteria. So for the recapitulation value the quality value of E-Comic Learning Media is 89.03% with very valid criteria. In implementation the researcher obtained the results of the responses of students and class teachers. At the validation stage, the media obtained an average of 91.87% with very valid criteria. Researchers in implementation distributed test sheets and got an average score of 89.48% with very good criteria. Then comic media is feasible and suitable for implementation.